TANGGUNG JAWAB PERDATA DOKTER DALAM MALPRAKTIK DITINJAU DALAM PERSFEKTIF HUKUM ISLAM - Suharna (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2022)
The purpose of this study is to determine the nature of the doctor's civil responsibility in malpractice and the sociological aspects of legal responsibility in medical malpractice. This research is classified as descriptive qualitative. the researcher uses a sociological and syar'i approach, data is collected by quoting and analyzing using content analysis of literature or books that have relevance to the problems discussed and the opinions of jurists (Islamic jurists) then review and conclude. The results of this study indicate that the nature of the doctor's responsibility in malpractice to his patients is very risky and the medical profession must have high accuracy in its services to its patients. High accuracy in the medical profession indicates that the medical profession is full of risks. So not infrequently a doctor is often considered to have committed a crime or negligence in his actions which is often called medical malpractice, the ignorance of the community in distinguishing between malpractice, accident and negligence in medical action. The doctor-patient relationship is a legal relationship in a legal engagement. Legal engagement is a bond between two or more legal subjects to do something or not to do something or to give something article 1313 in conjunction with article 1234 burgerlijk wetboek in short BW which is called achievement. So based on the provisions of the law, there are three kinds of achievements, namely a legal obligation of one party to the other or vice versa the legal subject who makes the engagement. Reciprocal legal engagements always burden each other with obligations, in addition to giving birth to rights on each party. The obligation to provide achievements for one party (the debtor) becomes the right to receive achievements on the other party (the creditor). And vice versa.